No Rest for the Wicked? The Consequences of Incarceration for Sleep Problems. (November 2017) - Testa, Alexander; Porter, Lauren C.
About one in every five Americans suffers from inadequate sleep, a key indicator of physical and mental well-being. Using data from the National Longitudinal Study of Adolescent Health, we investigate the association between incarceration and two related sleep problems: short sleep duration and symptoms of insomnia. We find that relative to those who have not been incarcerated, those with a history of incarceration have an elevated risk of short sleep duration and insomnia symptoms. These associations persist even after controlling for a host of potential confounders, including prior sleep problems. Additionally, the associations do not differ significantly across race.